The last Olympian - Riordan, Rick. (New York : Disney/Hyperion Books, 2011)
The long-awaited prophecy surrounding Percy Jackson's sixteenth birthday unfolds as he leads an army of young demigods to stop Kronos in his advance on New York City, while the Olympians struggle to contain the rampaging monster, Typhon.
Notable/Best Books (A.L.A.)
School Library Journal starred
Wilson's Junior High School
Book Links (A.L.A.), July 2008
Booklist starred, May 2009
Booklist, September 2005
Keywords: Animals, Mythical -- Juvenile fiction; Fate and fatalism -- Juvenile fiction; Monsters -- Juvenile fiction; Mythology, Greek -- Juvenile fiction; Titans (Mythology) -- Juvenile fiction; Animals, Mythical -- Fiction; Fantasy; Fate and fatalism -- Fiction; Monsters -- Fiction; Mythology, Greek -- Fiction; Titans (Mythology) -- Fiction; Fate and fatalism -- Fiction; Greek mythology -- Fiction; Monsters -- Fiction; Mythical animals -- Fiction; Titans (Mythology) -- Fiction; Fantastic fiction; Fantastic fiction